Protecting Water Resources from Agricultural Pesticides - O. Norman Nesheim; Frederick M. Fishel (EDIS)
Revised! PI-1, a 5-page illustrated fact sheet by O. Norman Nesheim and Frederick M. Fishel, describes practices that help protect groundwater and surface water from pesticide contamination. Includes references. Published by the UF Department of Agronomy, April 2009.